Simple Bithiophene–Rhodanine‐Based Small Molecule Acceptor for Use in Additive‐Free Nonfullerene OPVs with Low Energy Loss of 0.51 eV. Issue 16 (6th March 2019) - Lee, Taeho; Eom, Yoonho; Song, Chang Eun; Jung, In Hwan; Kim, Dongwook; Lee, Sang Kyu; Shin, Won Suk; Lim, Eunhee
Abstract: The introduction of rigid and extended ladder‐type fused‐ring cores, such as indacenodithiophene, has enabled the synthesis of a variety of nonfullerene small molecules for use as electron acceptors in high‐performance organic photovoltaic cells. Contrasting with recent trends, a very simple‐structured nonfullerene acceptor (NFA), T2‐ORH, consisting of a bithiophene core and octyl‐substituted rhodanine ends, is synthesized in two steps from inexpensive commercially available raw materials. Its relatively short π‐conjugation results in a wide bandgap and a blue‐shifted UV–vis absorption profile complementary to those of poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐co‐3‐fluorothieno[3, 4‐b]thiophene‐2‐carboxylate] (PTB7‐Th). Despite a sufficient offset betweenT2‐ORH and PTB7‐Th, the lowest unoccupied molecular orbital (LUMO) energy level ofT2‐ORH is still higher than the LUMOs of other NFAs (e.g., ITIC). Therefore, the PTB7‐Th:T2‐ORH blend film exhibits an efficiency of 9.33% with a high open‐circuit voltage of 1.07 V and a short‐circuit current of 14.72 mA cm −2 in an additive‐free single‐junction cell. Importantly, the optimized device displays a remarkably low energy loss of 0.51 eV, in which bimolecular and monomolecular charge recombination is effectively suppressed by solvent vapor annealing treatment. The blend film has a very smooth and homogeneous morphology, providing both vertical and parallel charge transport in the devices. Abstract : A very simple rod‐shaped bithiophene‐based small molecule, T2‐ORH, is synthesized in only two steps to obtain a nonfullerene acceptor for use in efficient organic photovoltaic cells. The additive‐free inverted PTB7‐Th:T2‐ORH single‐junction device exhibits a power conversion efficiency of 9.33%, with a remarkably low E loss of 0.51 eV due to a smooth homogeneous film morphology and vertical and parallel charge transport.